The Influence of the Use of Social Media of Educational Institutions on the Fulfillment of Student Information Needs - Putriani, Regita; Reza, Faisal; Putri, Shinta Hartini; Lathifah, Nisa (Sinergi International Journal of Communication Sciences, 2023)
Instagram is a social media used to interact with other users and offers various features provided by Instagram such as Direct Message, Like, and Comment. The phenomenon of the teaching and learning process in higher education is also inseparable from technological advances, both from curriculum development, academic systems to student activities. One of the utilization of technological advances is the dissemination of information about the campus world. The implementation of Uses and Gratification Theory in this study can be seen from individual active students who deliberately seek information and become followers of the @academic_csunibi Instagram account as a fulfillment of information needs. This study aims to determine the effect of using instsgram social media on the @academik_csunibi account on fulfilling the information needs of active students of Universitas Informatika and Bisnis Indonesia Academic Year 2019-2022. The research method used is a quantitative method with a verificative approach. The population in this study were active students of the University of Informatics and Business Indonesia in the 2019-2022 academic year with a sample size of 100 respondents with purposive sampling technique. The results of this study indicate that in the T test data from the results of the IBM SPSS 23 statistical data analysis obtained data of 8,364> 1654, it means that H0 is rejected and H1 is accepted, so this value indicates that there is an influence between the collaboration sub variable on the current need approach variable.